Maternal serum zinc levels and urinary tract infections among pregnant women at a tertiary hospital in Lusaka, Zambia: a cross-sectional study - Musaba, John; Mukosha, Moses; Mukololo, Lubinda; Vwalika, Bellington (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Micronutrient deficiency is one of the leading public health problems, particularly in lower-middle-income countries. The link between serum zinc (Zn) levels and urinary tract infections (UTIs) among pregnant women is still poorly understood. We investigated the association between maternal serum Zn levels and UTIs among pregnant women at women and newborn hospital in Lusaka, Zambia. Methods: We conducted an analytical cross-sectional study among 228 pregnant women aged 18 to 45 years between 1 September and 30 November 2019. Serum Zn levels were measured using atomic absorption spectrophotometry (AAS), whereas UTIs were determined based on the local hospital guidelines. We used the logistic regression model to determine the association between Zn levels and UTIs. The analysis was done at a significance level of 5% and 95% confidence interval. Results: Of the total participants, 118/228 (51.75%) tested positive for UTIs from urine culture. The mean serum Zn levels in the group diagnosed with UTIs were 53.95 ug/dl (SD=35.10), while in those who had no UTIs, it was 50.05 ug/dl (SD=35.10). In a multivariable logistic regression analysis, we found no evidence of an association between serum Zn levels and UTIs (p=0.435). Conclusions: From the study findings, there was no association between serum Zn levels and UTIs. This result suggests that Zn may not have any role in urinary tract infection. Nevertheless, more extensive studies are needed to confirm our findings.